Management Issues for Adolescents with Cystic Fibrosis - Adelaide Lindsay Withers (Pulmonary Medicine)
The healthy adolescent will encounter major changes in biological and psychosocial domains. The adolescent period can be greatly affected by a chronic illness. Cystic fibrosis is a terminal illness that can significantly affect an adolescent’s biological, mental and psychosocial health. This paper discusses general issues to consider when managing an adolescent with a chronic medical condition, and specifically how cystic fibrosis may impact upon puberty, body image, risk-taking behaviours, mental health, independence, nonadherence, reproductive health, transition, lung transplantation, and end of life care.